2020
DOI: 10.36782/i-pop.v1i1.33
|View full text |Cite
|
Sign up to set email alerts
|

Self-Styling, Popular Culture, and the Construction of Global-Local Identity among Japanese Food Lovers in Purwokerto

Abstract: People are currently faced with the kaleidoscopic flux of dishes, that almost everyone encounters various foods from around the world, one of which is Japanese Food. The presence of Japanese food in Purwokerto City, Central Java is the consequence of the global power with its capability to produce thoughts and ideas, real or illusory, related to their products and all of which influence local values and cultures. This research studies the impacts of globalization as reflected in the formation of identity and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…A research investigation into the culinary inclinations of Indonesian adolescents has revealed that authentic Indonesian cuisine, including dishes such as Nasi Goreng (an Indonesian rendition of fried rice) and Sate (a grilled meat skewer delicacy), remains the foremost choice of food. Nevertheless, the investigations established that the emerging generation of Indonesian individuals display a growing inclination towards experimenting with diverse gastronomical cultures and venturing into global culinary alternatives (Andriyanty & Wahab, 2022;Fatikhani & Setiawan, 2019;Lusiana et al, 2020) The dietary preferences of Indonesian adolescents have undergone significant changes in recent years owing to the changes in their lifestyle, urbanization, and globalization. Although traditional Indonesian cuisine continues to maintain its popularity, there has been a marked increase in the consumption of Western-style fast food, processed snacks, and sugary beverages within this demographic.…”
Section: Current Lifestyle Of Indonesia's Multicultural Youthmentioning
confidence: 99%
“…A research investigation into the culinary inclinations of Indonesian adolescents has revealed that authentic Indonesian cuisine, including dishes such as Nasi Goreng (an Indonesian rendition of fried rice) and Sate (a grilled meat skewer delicacy), remains the foremost choice of food. Nevertheless, the investigations established that the emerging generation of Indonesian individuals display a growing inclination towards experimenting with diverse gastronomical cultures and venturing into global culinary alternatives (Andriyanty & Wahab, 2022;Fatikhani & Setiawan, 2019;Lusiana et al, 2020) The dietary preferences of Indonesian adolescents have undergone significant changes in recent years owing to the changes in their lifestyle, urbanization, and globalization. Although traditional Indonesian cuisine continues to maintain its popularity, there has been a marked increase in the consumption of Western-style fast food, processed snacks, and sugary beverages within this demographic.…”
Section: Current Lifestyle Of Indonesia's Multicultural Youthmentioning
confidence: 99%
“…Pertama, perlunya mengkaji lebih lanjut kemungkinan (Wahab et al, 2018). Popularitas masakan Jepang di Indonesia saat ini terus meningkat (Lusiana et al, 2020), dengan demikian penurunan beras kepala varietas Tarabas yang diberi perlakuan paclobutrazol kemungkinan dapat memengaruhi tingkat adopsi teknologi oleh petani.…”
Section: Implikasi Penelitianunclassified
“…In fact, each locality has its own values and wisdom to become a means of diplomacy in international relations (Pujayanti, 2017;Utami, 2018). In fact, globalization with the media as its agent is actually, in addition to contributing to the formation of identity, on the other hand, it also provides an opportunity to stimulate the promotion of heterogeneous behavior through forms of appropriation (Lusiana et al, 2020) This opportunity is certainly interesting to explore, considering that Indonesian cuisine is very diverse in forms, origin of ingredients, and ways of serving according to the origin of the region (Setiawan, 2016;Wijaya, 2019). One of them is Banyumas Regency in Central Java Province, which has a number of local specialties with authentic flavors, such as getuk or mendoan.…”
Section: Introductionmentioning
confidence: 99%